In the borderland between song and speech Vocal expressions in oral cultures - Lundström, Håkan; Svantesson, Jan-Olof (Lund University Press, 2022)
This book focuses on vocal expressions in the borderland between song and speech. It spans across several linguistic and musical milieus in societies where oral transmission of culture dominates. 'Vocal expression' is an alternative word for 'song' which is free from bias based on cultural and research-related traditions. The borderland between song and speech is a segment of the larger continuum that extends from speech to song. These vocal expressions are endangered to the same degree as the languages they represent. Perspectives derived from ethnomusicology, prosody, syntax, and semantics are combined in the research, in which performance templates serve as an analytical tool. The focus is on the techniques that make performance possible and on the transmission of these techniques. The performance templates serve to organize the vocal expression of words by combining musical and linguistic conventions. It is shown that all the cultures studied have principles for organizing these parameters; but each does this in its own unique way while meeting a number of basic needs on the part of human society, particularly communal interaction and interaction with the spirit world. A working method is developed that makes it possible to gain qualitative knowledge from a large body of material within a comparatively limited period of time.